Improving the Selected Life Science Competencies of Grade 11 Learners with Special Needs through Parent - Assisted Learning Plan - Valencia, Mark Janree L.; Sagnep, Joy Marie T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
COVID-19 has transformed education delivery and doubled the challenges of learners with special needs (LSENs) due to inaccessible assistive technologies and limited face-to-face interaction with special education teachers. Consequently, their parents were forced to teach without formal training (World bank, 2020). Thus, this sequential mixed method study aimed to improve the learners' selected Life Science competencies in animal reproduction, genetic engineering, animal survival, and evolution through Parent-Assisted Learning Plan (PALP). The PALP is a 3-week home instruction cycle introduced to the participants where the teacher who created the self-learning modules met one-on-one with the home learning facilitators (HLFs) to discuss the various concepts covered in the modules emphasizing real-world applications and demonstrating strategies in teaching the concepts to the participants at home. Six Grade 11 LSENs from Ferdinand E. Marcos Senior High School participated in this study. The data came from validated 50-item teacher-created tests and focus group discussions. Frequency, percentage, means, and t-test was used to analyse quantitative data, while thematic analysis was applied for qualitative data. The t-test results show that PALP effectively improves learners' selected Life Science competencies. However, the participants also faced problems, including the difficulty of lessons, poor information retention, and a lack of formal sign language training among home learning facilitators. It is then recommended that schools may adopt and implement the PALP to help LSENs cope with the new learning delivery.